2001
DOI: 10.2337/diabetes.50.3.573
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance With Enhanced Insulin Signaling in High-Salt Diet–Fed Rats

Abstract: Previous clinical studies showed an apparent correlation between hypertension and insulin resistance, and patients with diabetes are known to have increased blood pressure responsiveness to salt loading. To investigate the effect of high salt intake on insulin sensitivity and the insulin signaling pathway, a high-salt diet (8% NaCl) or a normal diet was given to 7-week-old SD rats for 2 weeks. High salt-fed rats developed slightly but significantly higher systolic blood pressure than controls (133 ؎ 2 vs. 117 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
87
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 52 publications
15
87
3
Order By: Relevance
“…Preparation of the antibodies An antibody against the whole mouse resistin molecule was prepared by immunising rabbits with the recombinant mouse resistin protein, obtained as described previously [21]. Sequences corresponding to nucleotides 11-173 of RELMβ/FIZZ2 and 47-227 of RELMγ/FIZZ4 were amplified by PCR and cloned into the pGEX-3T expression vector (Pharmacia, Piscataway, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of the antibodies An antibody against the whole mouse resistin molecule was prepared by immunising rabbits with the recombinant mouse resistin protein, obtained as described previously [21]. Sequences corresponding to nucleotides 11-173 of RELMβ/FIZZ2 and 47-227 of RELMγ/FIZZ4 were amplified by PCR and cloned into the pGEX-3T expression vector (Pharmacia, Piscataway, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were centrifuged at 3,000 rev/min for 20 min and sera containing equal amounts of protein were used for immunoprecipitation. Immunoblotting against these immunoprecipitates was performed as previously described [21]. Animal care and procedures of the experiments were approved by the Animal Care Committee of the University of Tokyo.…”
Section: Methodsmentioning
confidence: 99%
“…The results shown are the representative data from triplicate experiments. 47). Recently, Qiao et al (35) reported the presence in the hepatic cytosols of a genetically diabetic rat of a kinase responsible for the Ser 789 phosphorylation of IRS-1, which was distinct from AMPK.…”
Section: Sik2 Is Activated In White Adipose Tissues Of Diabetic Mice-mentioning
confidence: 99%
“…The rats were then killed by intracardiac injection of pentobarbital. Isolated soleus muscle was incubated for 20 min with or without 1.44×10 −8 mol/l human insulin (this concentration is equivalent to 2 mU/ml), as described previously [17]. 2-Deoxy glucose uptake into the isolated soleus muscle strips was measured using 2-deoxy-D-[ 3 H]glucose and [ 14 C]manitol as described previously [21].…”
Section: Introductionmentioning
confidence: 99%
“…Rats fasted overnight were anaesthetised by intraperitoneal injection of pentobarbital sodium (60 mg/kg body weight) and the left jugular and femoral veins were catheterised for blood sampling and infusion respectively. Hyperinsulinaemic-euglycaemic clamp analysis was performed as described previously [17]. The glucose utilisation rate, hepatic glucose production and an estimate of muscle glucose uptake during the clamp (defined as the glucose metabolic index) were calculated as previously described [20].…”
Section: Introductionmentioning
confidence: 99%